Phase II Trial of SBRT for Stage I NSCLC: Survival, Local Control, and Lung Function at 36 Months. Issue 7 (July 2016) - Navarro‐Martin, Arturo; Aso, Samantha; Cacicedo, Jon; Arnaiz, Maria; Navarro, Valentin; Rosales, Samuel; de Blas, Rodolfo; Ramos, Ricard; Guedea, Ferran
ABSTRACT : Objectives: : The long‐term impact of stereotactic body radiotherapy (SBRT) on respiratory function in patients with inoperable non–small cell lung cancer (NSCLC) has not been well studied. The aim of this phase II trial was to assess local control, survival, and lung function at 36 months after treatment. Methods: : From July 2008 to February 2012, 42 patients in whom inoperable NSCLC with peripheral lesions was diagnosed were consecutively enrolled. Lung function testing included measurement of forced expiratory vital capacity, forced expiratory volume in 1 second, and diffusing capacity for carbon monoxide. All lung function parameters were registered at baseline and evaluated prospectively after SBRT every 6 months for 2 years and annually thereafter. Results: : Of the 42 initial patients, four were excluded. At 36 months after SBRT, 22 patients were still evaluable (12 deaths and four patients lost to follow‐up). At 36 months, the rate of local control was 94%. At 1, 2, and 3 years, respectively, overall survival rates were 92%, 75%, and 66%. Median overall survival was 57 months. Grade (G) 3 acute toxicity was observed in four patients (10%). Chronic G1 toxicity was observed in all 38 cases (100%), with the most common type being pneumonitis (26 patients [68%]). The mean lung function parameters at baseline and at 36 months after treatment were as follows: forced expiratory vital capacity 83% versus 79%; forced expiratory volume in 1 second 62% versus 57%; and diffusing capacity for carbon monoxide 54% versus 54%. These changes were not significant. Conclusions: : In this trial, local control and survival rates after SBRT were very good. Treatment with SBRT had no significant impact on lung function at 36 months. These findings provide further support for the use of SBRT as a radical treatment for NSCLC. Lung toxicity is minimal, even in patients with poor pulmonary function before treatment.